(untitled) (Web of Teachers: Inderscience Research, 2025)
Cerebral Palsy (CP) is one of the most complex neurological disorders in children, arising from brain damage before birth, during delivery, or in early childhood. This condition is characterized not only by motor and muscle function impairments but also by dysfunctions in cognitive, emotional, and sensory systems. A thorough analysis of the causes, neurological features, and rehabilitation methods for CP is crucial for improving patients’ quality of life.